(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
The modernization of higher education requires the integration of innovative pedagogical technologies that enhance the effectiveness of teaching and learning processes. Physical education in higher education institutions plays an essential role in promoting students’ physical development, health culture, and active lifestyle. However, traditional teaching approaches in physical education often focus primarily on repetitive physical exercises and do not fully consider modern educational technologies that can increase students’ motivation and engagement. This study examines the effectiveness of applying innovative pedagogical technologies in physical education classes at higher education institutions. The research analyzes contemporary teaching approaches including interactive learning, digital monitoring tools, game-based activities, differentiated instruction, and student-centered methods. These technologies contribute to improving students’ physical performance, developing motor skills, and strengthening their interest in regular physical activity. The study also highlights the role of digital tools such as mobile fitness applications, video analysis systems, and performance tracking platforms that enable teachers to evaluate students’ progress more accurately. The findings indicate that innovative pedagogical technologies significantly improve the quality of physical education lessons by making them more dynamic, individualized, and interactive. As a result, students demonstrate higher levels of participation, better mastery of physical exercises, and increased awareness of healthy lifestyle practices. The research emphasizes the importance of methodological modernization in physical education and suggests that the systematic implementation of innovative teaching technologies can substantially improve the educational outcomes of physical education programs in higher education institutions.